New Firm Registration and the Business Cycle - Klapper, Leora; Love, Inessa; Randall, Douglas (World Bank, Washington, DC, 2014)
This paper uses new panel data on the number of new firm registrations in 109 countries during 2002-2012 to study the relationship between entrepreneurship and economic growth. The data show strong evidence of a pro-cyclical pattern in entrepreneurship. An examination of heterogeneous relationships between new firm registration and the business cycle finds that higher levels of financial development and better business environments are associated with stronger pro-cyclicality of entrepreneurship both across countries and within countries over time. The results are robust to various measures of business regulation, such as the cost and time of starting a new firm and closing an insolvent firm. These findings suggest that fostering an efficient regulatory environment for the financial and private sector is important for encouraging a speedier recovery in the formation of new firms during economic expansions and aiding the efficient wind-down of insolvent firms during economic slowdowns.